Working With(in) the Shadow of Experiential Learning. (February 2019) - Elmes, Michael B.
This article explores the shadow dynamics of experiential learning using a psychodynamic perspective. It reviews the concept of shadow at the individual, group, and intergroup levels and draws on a short case from the author's experiences to consider how shadow dynamics may arise quickly and unexpectedly to take over the experiential learning classroom. It considers what the author learned about the shadow from the experience and how he conducts the experiential learning activity differently now to facilitate greater self-understanding and deeper learning.